The Influence of Work-Life Balance and Flexible Working Arrangements on Auditor Performance at the Bengkulu Provincial Inspectorate - Intan Nur Fitriani; Novita Sari; Halimatusyadiah (LP2M IAIN Palopo, 2026)
This research is motivated by the persistent performance issues of auditors at the Bengkulu Provincial Inspectorate, reflected in findings on regional financial management and the potential for role conflict due to high work demands. This condition requires attention to non-technical factors such as work-life balance and flexible working arrangements. This study aims to examine the effect of work-life balance and flexible working arrangements on auditor performance. The research method uses a quantitative approach with a survey method. The study population was all 62 auditors at the Bengkulu Provincial Inspectorate, sampled through a saturated sampling technique. Data were collected using a questionnaire and analyzed using multiple linear regression using SPSS. The results show that work-life balance has a positive and significant effect on auditor performance, as does flexible working arrangements, which also have a positive and significant effect. Simultaneously, both variables are able to explain 53.3% of the variation in auditor performance. In conclusion, improving work-life balance and implementing optimal work flexibility can improve auditor performance. The implications of this study emphasize the importance of organizational policies that support work well-being and flexibility as a strategy to improve the performance of public sector auditors.